DETERMINAN PERILAKU INISIASI MENYUSU DINI PADA IBU POSTPARTUM DI TIGA KECAMATAN KOTA TANGERANG TAHUN 2022 - Nelvioni Devita Tupitu, (2023)
Early initiation of breastfeeding can prevent 22% of infant deaths in developing countries. This study aims to determine the factors that influence the behavior of Early Breastfeeding Initiation in postpartum mothers in three district Tangerang City (Karawaci Sub-District, Tangerang Sub-District and Priuk Sub-District). The research method used is descriptive analytic with a cross-sectional. This research was conducted on 84 post-partum mothers using a questionnaire with the chi-square statistical test. The population of this study were post-partum mothers in three sub-districts of Tangerang City, namely Karawaci Sub-District, Tangerang Sub-District and Priuk Sub-District, who gave birth in a health care facility in health centers, maternity clinics and hospitals in Tangerang City. The results of the chi-square test obtained p = 0.001 for age, p = 0.015 for educational level, p = 0.002 for occupation, p = 0.108 for income, p = 0,758 for parity, p = 0.001 for history of Covid-19, p = 0.000 for knowledge, p=0,831for mother's attitude, p = 0.000 for health services, p = 0.000 for the support of health workers and p = 0,361 for family support. Multivariate analysis showed that health personnel support (p=0,013) had the dominant correlation with early breastfeeding initiation behavior in post-partum mother Exp (B) =25.753; Cl=1,996-332,245. The conclusion of the study showed that there was a significant relationship between age, education, occupation, history of Covid-19, knowledge, health services and support from health workers with the early breastfeeding initiation behavior in post-partum mothers.